Controlling output pulse and prepulse in a resonant microwave pulse compressor; Journal of Applied Physics; Vol. 113, iss. 5 - Shlapakovski A.; Artemenko S. N. Sergey Nikolaevich; Chumerin P. Yu. Pavel Yurievich; Yushkov Y. G. Yuri Georgievich (2013, 2013)
Title screen